Data_Sheet_1_Diversity of RNA viruses of three dominant tick species in North China.docx - Tong Qin; Mingjie Shi; Meina Zhang; Zhitong Liu; Hao Feng; Yi Sun (2023)
Background A wide range of bacterial pathogens have been identified in ticks, yet the diversity of viruses in ticks is largely unexplored. Methods Here, we used metagenomic sequencing to characterize the diverse viromes in three principal tick species associated with pathogens, Haemaphysalis concinna, Dermacentor silvarum, and Ixodes persulcatus, in North China. Results A total of 28 RNA viruses were identified and belonged to more than 12 viral families, including single-stranded positive-sense RNA viruses (Flaviviridae, Picornaviridae, Luteoviridae, Solemoviridae, and Tetraviridae), negative-sense RNA viruses (Mononegavirales, Bunyavirales, and others) and double-stranded RNA viruses (Totiviridae and Partitiviridae). Of these, Dermacentor pestivirus-likevirus, Chimay-like rhabdovirus, taiga tick nigecruvirus, and Mukawa virus are presented as novel viral species, while Nuomin virus, Scapularis ixovirus, Sara tick-borne phlebovirus, Tacheng uukuvirus, and Beiji orthonairovirus had been established as human pathogens with undetermined natural circulation and pathogenicity. Other viruses include Norway mononegavirus 1, Jilin partitivirus, tick-borne tetravirus, Pico-like virus, Luteo-like virus 2, Luteo-likevirus 3, Vovk virus, Levivirus, Toti-like virus, and Solemo-like virus as well as others with unknown pathogenicity to humans and wild animals. Conclusion In conclusion, extensive virus diversity frequently occurs in Mononegavirales and Bunyavirales among the three tick species. Comparatively, I. persulcatus ticks had been demonstrated as such a kind of host with a significantly higher diversity of viral species than those of H. concinna and D. silvarum ticks. Our analysis supported that ticks are reservoirs for a wide range of viruses and suggested that the discovery and characterization of tick-borne viruses would have implications for viral taxonomy and provide insights into tick-transmitted viral zoonotic diseases.